Developing Proportional Reasoning via Lego Robotics: Experiences of a 7th Grade Mathematics Class - Shelli L Casler-Failing; Leah C Swann (Middle Grades Review, 2023)
A qualitatively oriented mixed methods case study was conducted to investigate the effects of incorporating LEGO robotics into a seventh-grade mathematics curriculum. Using the lenses of Social Constructivist Theory and the Five Stages of Technology Integration, this research focused on the development of proportional reasoning skills. The data show students experienced success in developing their proportional reasoning skills as they completed tasks using the robotics. The quantitative data shows evidence of growth in understanding and development of proportional reasoning. The qualitative analysis provides evidence that students developed their understanding through collaborative discussions as they worked through the different technology stages. Overall, students enjoyed the opportunity to learn with the robotics because it was hands-on and applicable to their lives.
Keywords: Lego robotics; mathematics; proportional reasoning; technology